2007
DOI: 10.1111/j.1939-1676.2007.tb01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom‐Derived Maitake PETfraction as Single Agent for the Treatment of Lymphoma in Dogs

Abstract: Background: Maitake PETfraction is a standardized essence extracted from the mushroom Maitake (Grifola frondosa) that has antitumor activity in tumor-bearing mice. In addition, PETfraction induces apoptosis in human prostate and bladder cancer cells and suppresses the proliferation in vitro of several canine tumor cell lines, such as lymphoma (Cl-1), mammary gland (CF33), and connective tissue (CF21).Hypothesis: Maitake PETfraction is effective as a single agent in dogs with lymphoma. Animals: Fifteen dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Research investigating use of mushroom supplements in cancer treatment is more extensive; however, the results are conflicting. in vitro and in vivo studies of human and murine cancers provide evidence that mushroom supplements may be a useful complementary cancer treatment, 28‐31 while a prospective non‐controlled in vivo study of 15 dogs with lymphoma found no objective response to the treatment 32 . Clinicians should be aware of these growing trends and be equipped with evidence‐based knowledge when providing nutritional advice, especially following a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating use of mushroom supplements in cancer treatment is more extensive; however, the results are conflicting. in vitro and in vivo studies of human and murine cancers provide evidence that mushroom supplements may be a useful complementary cancer treatment, 28‐31 while a prospective non‐controlled in vivo study of 15 dogs with lymphoma found no objective response to the treatment 32 . Clinicians should be aware of these growing trends and be equipped with evidence‐based knowledge when providing nutritional advice, especially following a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to technical difficulties, few studies have yet been performed to determine the attainable physiological concentrations of PET-F in animals. However, PET-F has been studied in dogs bearing intermediate or high-grade lymphomas with an expected survival time of 2 weeks [19]. Such study showed that PET-F was well tolerated in these dogs but no significant improvements or cancer regression was seen with PET-F administration.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is also important to address the safety of PET-F for a therapeutic utility. In addition to the above PET-F study on dogs with lymphomas [19], a few toxicity studies of PET-F have also been performed in animals. For instance, a toxicity study using healthy beagle dogs (n = 10) confirmed that no toxicity was seen in any dogs when they received PET-F (3.3 mg/ kg body weight per day) for 10 weeks [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a research survey, the effect of triterpenes isolated from the mycelial extract of Ganoderma lucidum shows arrest of cell cycle in G2-M phase of human leukaemia cancer cell lines HT-29 (Muller et al 2006). Grifolan frondosa PET fraction extracts are used for the treatment of leukaemia in dogs, to induce apoptosis and suppress proliferation of lymphoma C-1 cell lines in vitro (Griessmayr et al 2007).…”
Section: Leukaemiamentioning
confidence: 99%